(untitled) (Web of Teachers: Inderscience Research, 2025)
This article explores the significance of role-playing by analyzing its key components, including objectives, functions, role content, and the socio-psychological and didactic conditions that shape its implementation. Additionally, it examines the structural connections that ensure the coherence of role-playing in response to various external and internal changes. The role itself is regarded as a fundamental element of the educational and communicative context, reflecting its core parameters.